Framing Comparison of Netanyahu's Denial of the Gaza Famine in Al Jazeera and CNN Arabic - Muhammad Nur; Abdul Basid (Universitas Islam Negeri Palopo, 2025)
This study investigates the critical role of media framing in geopolitical conflict by analyzing the coverage of Israeli Prime Minister Benjamin Netanyahu's denial of the Gaza famine, a claim directly contradicted by international humanitarian reports. Employing a qualitative descriptive approach grounded in Robert Entman's framing theory (Problem Definition, Causal Diagnosis, Moral Judgment, and Suggested Remedies), we conducted a comparative analysis of news articles from two ideologically distinct outlets: Al Jazeera Arabic and CNN Arabic. The analysis reveals fundamentally divergent framing strategies. Al Jazeera utilized a decisive Accountability Frame, defining the problem as a